Targeting the Warburg and Q Effect: Novel Strategy to Disrupt Cancer Metabolism - Mohamed, Mahmoud Adel (AUC Knowledge Fountain, 2023)
One of the hallmarks of cancer cells is their altered metabolism, which serves their need to grow and proliferate. Cancer cells exhibit a marked increase in glucose consumption (Warburg effect). In addition, cancer cells also exhibit excessive uptake of glutamine, for biomass synthesis and for energy production through mitochondrial substrate level phosphorylation (glutaminolysis pathway). Glutamine metabolism is enhanced upon inhibition of glycolysis, also interference of glutamic metabolism leads to upregulation of glucose metabolism. So, simultaneous inhibition of glycolysis and glutaminolysis presents promising metabolic intervention strategy. In this study, we investigated high dose Vitamin C mechanism of action through MTT assays revealing Vitamin C as a selective inhibitor of glycolysis in cancer cells through NAD+ depletion. Also, we tested cytotoxicity of inhibitors of glutaminolysis and in combination with high dose vitamin C in two different cell lines, showing more effectiveness in combination than each treatment alone. In conclusion, we are proposing a novel combination of high dose ascorbic acid and inhibitor of glutaminolysis as a therapeutic cancer intervention.